Development and validation of a tool to evaluate resilience performance in metalworking industry - Fernandes, J. (2021)
For several organizations, occupational risk management is focused on risk assessment, accident investigation and analysis, and implementation of control measures. Investigation and analysis of accidents is often carried out taking into account causation models, with the objective of identifying the causes and determining effective corrective measures to improve both current practices and risk control systems. This behavior of the organizations fits in the traditional perspective of safety, realized as the absence of unwanted events